Turbidity Currents Can Dictate Organic Carbon Fluxes Across River‐Fed Fjords: An Example From Bute Inlet (BC, Canada). Issue 6 (9th June 2022) - Hage, S.; Galy, V. V.; Cartigny, M. J. B.; Heerema, C.; Heijnen, M. S.; Acikalin, S.; Clare, M. A.; Giesbrecht, I.; Gröcke, D. R.; Hendry, A.; Hilton, R. G.; Hubbard, S. M.; et al.
Abstract: The delivery and burial of terrestrial particulate organic carbon (OC) in marine sediments is important to quantify, because this OC is a food resource for benthic communities, and if buried it may lower the concentrations of atmospheric CO2 over geologic timescales. Analysis of sediment cores has previously shown that fjords are hotspots for OC burial. Fjords can contain complex networks of submarine channels formed by seafloor sediment flows, called turbidity currents. However, the burial efficiency and distribution of OC by turbidity currents in river‐fed fjords had not been investigated previously. Here, we determine OC distribution and burial efficiency across a turbidity current system within Bute Inlet, a fjord in western Canada. We show that 62% ± 10% of the OC supplied by the two river sources is buried across the fjord surficial (30–200 cm) sediment. The sandy subenvironments (channel and lobe) contain 63% ± 14% of the annual terrestrial OC burial in the fjord. In contrast, the muddy subenvironments (overbank and distal basin) contain the remaining 37% ± 14%. OC in the channel, lobe, and overbank exclusively comprises terrestrial OC sourced from rivers. When normalized by the fjord's surface area, at least 3 times more terrestrial OC is buried in Bute Inlet, compared to the muddy parts of other fjords previously studied. Although the long‐term (>100 years) preservation of this OC is still to be fully understood, turbidity currents in fjords appear to be efficient at storing OC supplied by rivers in their near‐surface deposits. Plain Language Summary: Plants on land use CO2 from the atmosphere to produce organic carbon, which promotes their growth. Rivers transport organic carbon to the sea, where it is either eaten by fauna or buried in the seafloor, thus decreasing atmospheric CO2 levels on Earth over thousands to millions of years. Fjords are recognized as global organic carbon sinks; trapping 18 million tons of organic carbon in their seafloor sediments each year. However, the complex morphology of fjord seafloors was not considered in the calculation of this organic carbon flux. In this study, we determine the distribution and abundance of terrestrial organic carbon across a fjord (Bute Inlet, Canada), which contains a submarine channel network terminating onto a large accumulation of sand (called a lobe). We show that 62% of the organic carbon supplied by the two rivers connected to the fjord is buried across the fjord; the majority of this carbon being held in the lobe. In total, Bute Inlet buries at least 3 times more organic carbon per unit of surface area than other fjords previously studied. Submarine channels in fjords thus appear to promote the storage of land‐derived organic carbon in the seafloor, potentially impacting CO2 levels and food resources for marine fauna. Key Points: Bute Inlet, a river‐fed fjord incised by turbidity currents, has a contemporary terrestrial organic carbon burial efficiency of 62% ± 10% Sandy surficial deposits are responsible for 63% ± 14% of the total terrestrial organic carbon burial budget in Bute Inlet, but only cover 17% of the seafloor area Global estimates based only on the muddy parts of fjords may significantly underestimate organic carbon burial rates by a factor >3